2008
DOI: 10.4049/jimmunol.180.11.7276
|View full text |Cite
|
Sign up to set email alerts
|

IL-15 Expands Unconventional CD8ααNK1.1+ T Cells but Not Vα14Jα18+ NKT Cells

Abstract: Despite recent gains in knowledge regarding CD1d-restricted NKT cells, very little is understood of non-CD1d-restricted NKT cells such as CD8+NK1.1+ T cells, in part because of the very small proportion of these cells in the periphery. In this study we took advantage of the high number of CD8+NK1.1+ T cells in IL-15-transgenic mice to characterize this T cell population. In the IL-15-transgenic mice, the absolute number of CD1d-tetramer+ NKT cells did not increase, although IL-15 has been shown to play a criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…Our finding of IL-15-mediated proliferation is in contrast to the lack of proliferation of iNKT cells observed in IL-15 Tg mice. 43 In this IL-15 Tg model, the excess IL-15 produced probably binds to the many cell types expressing IL-15R␣, which do not normally 27 we found that the presence of IL-15R␣ also increased the proliferation of immature hepatic CD44 High NK1.1 Ϫ cells. Because proliferation of immature CD44 High NK1.1 Ϫ cells was modulated by IL-15 in the liver but not in the thymus, it suggests that the type of IL-15 response is better dictated by the microenvironment than the stage of differentiation.…”
Section: Discussionmentioning
confidence: 68%
“…Our finding of IL-15-mediated proliferation is in contrast to the lack of proliferation of iNKT cells observed in IL-15 Tg mice. 43 In this IL-15 Tg model, the excess IL-15 produced probably binds to the many cell types expressing IL-15R␣, which do not normally 27 we found that the presence of IL-15R␣ also increased the proliferation of immature hepatic CD44 High NK1.1 Ϫ cells. Because proliferation of immature CD44 High NK1.1 Ϫ cells was modulated by IL-15 in the liver but not in the thymus, it suggests that the type of IL-15 response is better dictated by the microenvironment than the stage of differentiation.…”
Section: Discussionmentioning
confidence: 68%
“…A prominent population of CD8␣␣ TCR␣␤ cells was described in IL-15-transgenic animals (47). These cells were MHC class I dependent, since these were not observed in ␤ 2 -microglobulin knockout mice but were detected in CD1d knockout mice.…”
Section: Cd1mentioning
confidence: 95%
“…28,29 No significant variation in the proportions of CD161 ϩϩ , CD161 ϩ , and CD161 Ϫ cell populations was observed after culture ( Figure 7A). We found even without the addition of exogenous cytokines, by day 1 a CD8␤ low population is observed in all CD161 subsets ( ϩϩ , ϩ , and Ϫ ), which persists out to day 7 of culture ( Figure 7B).…”
Section: Cd161 ؉؉ Cd8␣␣ Cells Are Tissue Homing Type 17 T Cellsmentioning
confidence: 98%
“…However, they are consistent with murine data that suggest CD8␣␣ can be co-expressed on conventionally selected CD4, CD8␣␤ and DN T cells. 16,28,29,36,37 Culture experiments here used CD8 enriched PBMCs and so we are unable to comment on the possibility of induction of CD8␣␣ on CD4 and DN T cells in humans under similar experimental conditions. Given the existing mouse data, it will be important to look for these among gutderived lymphocytes in man.…”
mentioning
confidence: 99%